(3efXheI aj Yde GdWH GdeLQHs - (3GdOefghQj , CMeO Hf YHO GdefYe Hf jhSa Hf UjGe GdOefghQj, SQGL GdOjf,J (B1192 (3g` s
(3ChdgG (B:s
(3GdMeO ddg cGTa GdcQH Ke GdUdGI Ydi ef aGb cd fSH jGSGFdi Yf YdGL GdVQ edJeSkG deG jRjd GdCPi Yf cd edJeS s
(3BNQgG (B:s
(3ced GdfSN hGfbVi hcJHfG GdPi hLH QMe Gddg ef bQG hOYG ddPi cJH s
(3GdeDda cGf TjNkG ddCRgQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B164 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B303s
GAL - (3GdLRA (B2 - (3U (B499 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B269 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B297 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B_ (3GdQHGW (B(1493 (3O(B) s
Keywords: (3GdWHs